2009
DOI: 10.1158/1078-0432.ccr-09-1234
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab-Mediated Cell Signaling and Chemo/Immuno-sensitization of Drug-Resistant B-NHL Is Independent of Its Fc Functions

Abstract: Purpose: Rituximab [chimeric anti-CD20 monoclonal antibody], alone or combined with chemotherapy, is used in the treatment of non-Hodgkin's lymphoma (NHL). Rituximab binds to CD20 and inhibits intracellular survival/growth pathways leading to chemo/ immunosensitization of tumor cells in vitro. The contribution of rituximab Fc-FcR interaction in signaling is not known. This study examined the role of Fc-FcR interactions in rituximab-induced signaling using rituximab (Fab') 2 fragments as well as rituximab devoi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
41
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(48 citation statements)
references
References 32 publications
7
41
0
Order By: Relevance
“…on May 12, 2018. by guest www.bloodjournal.org From signaling pathways, including p38 mitogen-activated protein kinase, NF-B, and Akt, [58][59][60] and can increase chemotherapy-induced apoptosis in vivo. 61 Interestingly, long-term follow-up of one of the early phase 2 trials using R-CHOP in FL revealed that 7 of the 8 patients who were BCL-2 positive at baseline, subsequently became BCL-2-negative. 62 Two independent retrospective analyses of clinical studies in DLBCL demonstrated that the addition of rituximab to chemotherapy significantly improved overall survival over chemotherapy alone in patients with BCL-2-positive tumors, but not BCL-2-negative tumors, suggesting that patients with BCL-2-positive DLBCL have derived greater benefit from rituximab.…”
Section: Can We Improve Antitumor Responses Further By Inducing Direcmentioning
confidence: 99%
“…on May 12, 2018. by guest www.bloodjournal.org From signaling pathways, including p38 mitogen-activated protein kinase, NF-B, and Akt, [58][59][60] and can increase chemotherapy-induced apoptosis in vivo. 61 Interestingly, long-term follow-up of one of the early phase 2 trials using R-CHOP in FL revealed that 7 of the 8 patients who were BCL-2 positive at baseline, subsequently became BCL-2-negative. 62 Two independent retrospective analyses of clinical studies in DLBCL demonstrated that the addition of rituximab to chemotherapy significantly improved overall survival over chemotherapy alone in patients with BCL-2-positive tumors, but not BCL-2-negative tumors, suggesting that patients with BCL-2-positive DLBCL have derived greater benefit from rituximab.…”
Section: Can We Improve Antitumor Responses Further By Inducing Direcmentioning
confidence: 99%
“…Cell viability was assessed by either the trypan blue dye exclusion assay by microscopy or by the 2,3-bis(2-methoxy-4-nitro-S-sulfophenynl)H-tetrazolium-5 carboxanilide inner salt (XTT) dye absorbance according to the manufacturer's instruction (Roche Diagnostic GmbH) and as previously described (35). The viability of the untreated cells was set at 100%.…”
Section: Viability Assaymentioning
confidence: 99%
“…Ten microliters of nuclear proteins was mixed with the biotin probe for analysis of the transcription factors NFkB, Snail, and YY1, using the EMSA kits from Panomics, following the manufacturer's instructions and as previously described (35).…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of pathways, including the NF-κB, by rituximab has also been shown to sensitize lymphoma cells to cytotoxic drugs [44]. Further in vitro analysis that used a modified rituximab that lacked the Fc fragment determined that these rituximab-mediated effects were Fc-independent, without the need for FcR cross-linking, and occurred as a direct result of rituximab binding to CD20 [45]. Although these studies suggest a role for rituximab in promoting cell death, the contribution of this mechanism to the clinical therapeutic effects of rituximab across indications is still unclear.…”
Section: Cell Signaling and Apoptosismentioning
confidence: 99%